2013
DOI: 10.7448/ias.16.3.18670
|View full text |Cite|
|
Sign up to set email alerts
|

Testing the efficacy of an HIV stigma reduction intervention with medical students in Puerto Rico: the SPACES project

Abstract: IntroductionStigma associated with HIV has been documented as a barrier for accessing quality health-related services. When the stigma manifests in the healthcare setting, people living with HIV receive substandard services or even be denied care altogether. Although the consequences of HIV stigma have been documented extensively, efforts to reduce these negative attitudes have been scarce. Interventions to reduce HIV stigma should be implemented as part of the formal training of future healthcare professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The workshops were provided within students’ medical schools in order to facilitate voluntary attendance and participation. The results from our longitudinal study evidenced that the SPACES intervention was effective in reducing HIV/AIDS stigma attitudes and that such changes were still present at 12 month after having completed the intervention (Varas-Díaz et al, 2013). …”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The workshops were provided within students’ medical schools in order to facilitate voluntary attendance and participation. The results from our longitudinal study evidenced that the SPACES intervention was effective in reducing HIV/AIDS stigma attitudes and that such changes were still present at 12 month after having completed the intervention (Varas-Díaz et al, 2013). …”
Section: Introductionmentioning
confidence: 79%
“…We developed an intervention to reduce negative attitudes toward PLWHA among health professionals in training (Varas-Díaz et al, 2013). We named our intervention SPACES consistent with our promotional tagline of fostering “stigma free spaces in medical scenarios”.…”
Section: Introductionmentioning
confidence: 99%
“…The support strategy may reduce HIV stigma by changing stigmatizing behaviors of the people and, subsequently, increasing HIV test uptake (Doherty et al, 2013;Varas-Diaz et al, 2013). This was well illustrated in Uganda (Kaleeba et al, 1997) when interventions, such as providing counseling and social support, helped PLWH and their families cope with HIV and also changed people's stigmatizing behaviors and increased HIV test uptake.…”
Section: Mechanisms Of Stigma Reduction and Hiv Test Uptakementioning
confidence: 99%
“…An increased level of knowledge may change stigmatizing attitudes and subsequently change stigmatizing behaviors to reduce HIV stigma and increase HIV test uptake (Brown et al, 2003;Doherty et al, 2013;Stangl et al, 2013;Varas-Diaz et al, 2013). For example, Varas-Diaz et al (2013) and Perry, Fishman, Jacobsberg, Young, and Frances (1991) reported that education interventions were successful in increasing knowledge, changing stigmatizing attitudes and behaviors, and, subsequently,…”
Section: Mechanisms Of Stigma Reduction and Hiv Test Uptakementioning
confidence: 99%
“…Of these 21 studies, nine focused on attitudes toward PLWHA among health care professionals, including physicians and medical students. All nine of the studies were authored or co-authored by the same individual (Varas-Diaz et al, 2014;Nyblade et al, 2013;Varas-Diaz et al, 2013;Varas-Diaz et al, 2012;Varas-Diaz and Neilands, 2009;Varas-Diaz and Rodriguez, 2007;Ruiz-Torres et al, 2007).…”
Section: Previous Research Examining Hiv-related Stigma Toward Plwha mentioning
confidence: 99%